Modeling Instruction and the Nature of Science - Fishwild, Jon E. (My University, 2005)
High school students hold naïve conceptions about the nature of science (NOS),believing that scientific knowledge is absolute, that science is an objective activity without bias, creativity, or imagination, and that theories evolve into laws. The way in which science is taught in schools validates student misconceptions of the nature of science. Modeling instruction in physics is a teaching pedagogy, with Malcolm Wellsand Dr. David Hestenes the primary developers, that holds promise for conveying the tentative and empirical nature of scientific knowledge, the creativity and imagination that is required to create scientific knowledge, and the theory-laden nature of scientific knowledge. Research reports the necessity of explicitly referencing NOS themes within the classroom to improve student understanding of these themes. This investigation reports a quasi-experimental year-long study involving 65 students enrolled in a Midwestern suburban high school. All students received modeling instruction, but one group additionally received instruction using explicit reference to NOS themes within the context of the classroom laboratory experience and reflected on NOS themes while writing journals. The Views of Nature of Science-Form C (VNOS-C)measured student understanding in NOS using a pretest-posttest format. The Force Concept Inventory (FCI) assessed whether the NOS interventions adversely affected physics content knowledge of students in the treatment group. Students in the treatment group scored significantly greater on the VNOS-C( p < 0.05 ) than students in the comparison group. Students who receive explicit instruction in NOS themes are better able to articulate an understanding of NOS themes that is consistent with reform documents published by the American Association for the Advancement of Science and the National Research Council. Additionally, FCI results show that students who receive NOS interventions at the expense of additional content experience no deficit in their achievement of physics content knowledge, at least in the area of Newtonian mechanics. Modeling instruction provides a curricular structure that teaches physics students first-year concepts in Newtonian Mechanics. Teachers can enhance the modeling program to explicitly and purposefully target NOS themes within the laboratory context of the course, significantly improving student understanding of NOS without compromising student understanding of the physics content in mechanics.
Thesis chair, Dr. Virginia Epps. This file was last viewed in Adobe Reader 7.0
Keywords: Inquiry-based learning; Science--study and teaching